Csp–Csp bond cleavage and fragment coupling: a transition metal-free "extrusion and recombination" approach towards synthesis of 1, 2-diketones. Issue 19 (9th August 2021) - Gujjarappa, Raghuram; Vodnala, Nagaraju; Kandpal, Ashish; Roy, Lisa; Gupta, Sreya; Malakar, Chandi C.
Abstract : A metal-free strategy for C–C bond activation of 1, 3-diynes has been established via an "extrusion and recombination" approach to derive structurally important 1, 2-diketones in good yields with excellent selectivity. Abstract : A metal-free C–C bond activation strategy of 1, 3-diynes has been described via an "extrusion and recombination" approach, which delivered structurally important 1, 2-diketones. This phenomenon was performed using tetra- n -butylammonium iodide (TBAI) as a catalyst and peroxide as a radical initiator and oxidant. The C–C bond activation follows sequential oxidation, extrusion of CO2 as a byproduct and sewing of the molecular fragments to release the desired products. This protocol was elaborated towards unsymmetrical 1, 2-diketones via selective generation and recombination of distinct molecular fragments. The proposed mechanism has been verified using adequate control experiments and DFT calculations.